Methodological Guide for the Design, Implementation and Control of Integrative Assignments in the Human Morphophysiology Discipline - Luis Alberto Mass Sosa; Ana Margarita López Rodríguez del Rey; Milagros Lisett León Regal; Orlando Manuel Tomé López; Yanli Vazquez Villazón; Mileidis Yanelis Armas Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Integrative assignments support the development of communication skills and other skills leading to the improvement of critical thinking in students, a goal they need to meet in order both, to exchange and discuss criteria and to appreciate their social progress in the assimilation of contents. This article presents a methodological guide for the design, implementation and control of integrative assignments in the Human Morphophysiology discipline. This subject is included in the Basic Biomedical Sciences in Medicine Studies. The key aspects of this article are provided in three stages: description of the guide, guidelines to develop its various steps and some considerations to facilitate its use. An integral tasks-based system to work in groups, conceived from a systemic perspective of a new methodology in the classroom, contributes to the development of student-centered learning.